Book review: Wieczorek A., Schenk G. J., Juneja M., Lind C. (Eds.) (2014), Human. Nature. Disaster. From Atlantis till today [in German], Schnell und Steiner, Regensburg, Germany - Maria Bostenaru Dan (Urbanism. Arhitectura. Constructii, 2023)
The present article is a review of the book: Wieczorek A., Schenk G. J., Juneja M., Lind C. (Eds.) (2014), Human. Nature. Disaster. From Atlantis till today [in German], Schnell und Steiner, Regensburg, Germany, ISBN 978-3-7954-2880-8, 280 pages.